Edukasi pencegahan konsumsi alkohol pada remaja di SMK Muhammadiyah 3 Singosari Malang - Yoyok Bekti Prasetyo; Nurul Humaidi; Rahmad Wijaya (University of Muhammadiyah Malang, 2022)
Alcohol use in adolescents needs serious attention because of the negative impact on adolescent health and development. The prevalence of alcohol consumption among adolescents in Indonesia is 3.3% of them starting to drink at the age of 10, and most of them are traditional alcoholic beverages (38.7%). This community service program aims to reduce alcohol consumption among teenagers. There are two activities involved in this community service: education on alcohol prevention and screening of alcohol consumption. We carried the activity at Muhammadiyah 3 Singosari Vocational High School Malang. The participants were 57 students. This activity resulted in an increase in students' understanding of preventing alcohol consumption, with an average before the education of 5.40. In contrast, after being given education, it's score increased to 6.16. Most of the students at SMK do not consume alcohol or are shown in the normal category of 86.9%. However, some still consume 3.3% alcohol in the heavy category. This activity concludes that the provision of education can increase the understanding of adolescents, and then it is hoped that it will prevent alcohol consumption among adolescents. Follow-up efforts from the screening results are carried out by continuing to provide education, counseling, and further diagnostic examinations for adolescents.